Left Ventricular Assist Device as a Bridge to Recovery: Single Center Experience of Successful Device Explantation. Issue 6 (20th September 2022) - Zhang, Robert S.; Hanff, Thomas C.; Peters, Carli J.; Evans, Peter T.; Marble, Judy; Rame, J. Eduardo; Atluri, Pavan; Urgo, Kimberly; Tanna, Monique S.; Mazurek, Jeremy A.; Acker, Michael A.; Cevasco, Marisa; et al.
Abstract : Continuous-flow left ventricular assist devices (CF-LVAD) have been shown to enhance reverse remodeling and myocardial recovery in certain patients allowing for device removal. We sought to analyze the characteristics and describe outcomes of patients who underwent CF-LVAD explantation at a large academic center. We retrospectively identified all patients who underwent CF-LVAD explants due to recovery from 2006 to 2019. Patient baseline characteristics and data on pre- and postexplant evaluation were collected and analyzed. Of 421 patients who underwent CF-LVAD implantation, 13 underwent explantation (3.1%). Twelve HeartMate II and one HeartWare LVAD were explanted. All patients had nonischemic cardiomyopathy. Median time from heart failure diagnosis to LVAD implant was 12 months (interquartile range [IQR], 2–44) and the median time supported on LVAD was 22 months (IQR, 11–28). Two patients died within 30 days of explant. Three additional patients died during the follow-up period and all were noted to be nonadherent to medical therapy. After a mean follow-up duration of 5 years, overall survival was 52%. Mean pre-explant ejection fraction was 49%, which decreased at most recent follow-up to 32%. Mean pre-explant left ventricular internal diameter in diastole (LVIDD) was 4.37 cm and increased to 5.52 cm at most recent follow-up. Continuous-flow left ventricular assist device explantation is feasible and safe in select patients.